4-Methylanilinium 3-carboxy-2-hydroxypropanoate - S. Kalaiyarasi; S. Reena Devi; R. Akilan; R. Mohan Kumar; G. Chakkaravarthi (IUCrData, 2016)
The title molecular salt, C7H10N+·C4H5O5−, contains a 4-methylanilinium cation and a 3-carboxy-2-hydroxypropanoate (hydrogen 2-hydroxysuccinate) anion in the asymmetric unit. The cation is protonated at the amine N atom and the anion is deprotonated at one of the hydroxy O atoms of the carboxylic acid groups. An O—H...O hydrogen bond in the anion generates an S(5) graph-set motif. An N—H...O hydrogen bond links the anion and cation in the asymmetric unit. In the crystal, N—H...O and O—H...O hydrogen bonds link adjacent anions and cations, forming a two-dimensional network parallel to the ac plane and enclosing R23(12), R23(14) and R32(10) ring motifs.